Application of Methodology on System-Informational Analysis for Development of Efficient Dispatching Control Service in Power System - A. M. Huseynov; N. A. Yusifbeyli (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A method on selection and development of efficient hierarchical dispatching control service in power system has been considered on the basis of quantitative characteristics of integrity property. Taking development of dispatching control service in Azerbaijan power system the paper demonstrates the proposed method.